Spacer-thickness dependence of interlayer exchange coupling in GaMnAs/InGaAs/GaMnAs trilayers grown on ZnCdSe buffers. (March 2017) - Tivakornsasithorn, Kritsanu; Yoo, Taehee; Lee, Hakjoon; Choi, Seonghoon; Lee, Sanghoon; Liu, Xinyu; Dobrowolska, M.; Furdyna, Jacek K.
Abstract: Interlayer exchange coupling (IEC) between GaMnAs layers in GaMnAs/InGaAs/GaMnAs tri-layers was studied by magnetization measurements. Minor hysteresis loops are observed to shift in a direction indicating the presence of ferromagnetic (FM) IEC in the structures. The strength of the FM IEC clearly exhibits an exponential decrease with respect to nonmagnetic InGaAs spacer thickness. The fitting of the spacer thickness dependence of the FM IEC to an exponential decay function provides a decay length of 3.3±0.3 nm, which is relatively large compared to metallic multilayers, indicating a long ranged IEC in systems based on GaMnAs. Highlights: Interlayer exchange coupling (IEC) between GaMnAs layers with out-of-plane anisotropy has been investigated. The IEC between GaMnAs layers turned out to be ferromagnetic interaction. The strength of IEC monotonically decreases with GaAs spacer thickness. The IEC decay length of GaMnAs systems was an order of magnitude larger than that of metallic system.